The interpersonal communication book - De Vito, Joseph A.
The Interpersonal Communication Book balances theory and research with explication of practical skills to provide students with an in-depth understanding of interpersonal communication. With the concept of choice as its philosophical foundation, the book uses a threefold approach to assess communication: it examines the choices that are present in interpersonal situations, explains the theory and research that relates to these choices and provides the skills necessary to create effective messages.